2015
DOI: 10.1155/2015/902745
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Interscalene Nerve Block for Postoperative Pain Management in Patients after Shoulder Surgery

Abstract: Objectives. Shoulder surgery can produce severe postoperative pain and movement limitations. Evidence has shown that regional nerve block is an effective management for postoperative shoulder pain. The purpose of this study was to investigate the postoperative analgesic effect of intravenous patient-controlled analgesia (PCA) combined with interscalene nerve block in comparison to PCA alone after shoulder surgery. Methods. In this study, 103 patients receiving PCA combined with interscalene nerve block (PCAIB)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 24 publications
1
19
0
Order By: Relevance
“…Errors in documentation have the potential to skew results. Secondly, previous studies have shown that brachial plexus nerve blocks prior to shoulder surgery decrease postoperative opioid utilization[ 14 , 15 ], thus acting as a potential confounding variable. However, the proportion of patients receiving brachial plexus nerve blocks in this study was equivalent between study groups (Table 2 ) and thus did not likely affect the results.…”
Section: Discussionmentioning
confidence: 99%
“…Errors in documentation have the potential to skew results. Secondly, previous studies have shown that brachial plexus nerve blocks prior to shoulder surgery decrease postoperative opioid utilization[ 14 , 15 ], thus acting as a potential confounding variable. However, the proportion of patients receiving brachial plexus nerve blocks in this study was equivalent between study groups (Table 2 ) and thus did not likely affect the results.…”
Section: Discussionmentioning
confidence: 99%
“…We considered a difference of 20% in the mean 24-hour fentanyl consumption to be clinically significant. With an expected mean standard deviation of 150 mcg, expected mean 24-hour fentanyl consumption 500 μg,[ 5 ] an acceptable alpha error of 5%, and a power of the study of 80%, we required 28 patients in each group for a one-tailed analysis. Thus, with an added safety margin of 20%, we recruited 70 patients in the trial.…”
Section: Ethodsmentioning
confidence: 99%
“…The reason is that the detection of differences in pain is based on subjective scales (eg, visual analog scale), and the amount of opioids used long term, after surgery, is subject to recall bias or depends on how honest a patient is. 10,27 In addition, many patients might fill an opioid prescription but not take the medication. In the last case, the number of opioid prescriptions filled is not representative of the amount of opioid consumed by the patient.…”
mentioning
confidence: 99%
“…In the last case, the number of opioid prescriptions filled is not representative of the amount of opioid consumed by the patient. 10,23,39 Additional factors must be considered when investigating the pattern of opiate usage in surgical patients, as they constitute potential confounders. For example, any patient with a medical history of drug dependency or addiction is at higher risk for postoperative opiate misuse.…”
mentioning
confidence: 99%